2019
DOI: 10.7759/cureus.4954
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Breast Lesions Using a Novel Combined Approach of Ultrasonography and Elastography Prior to Invasive Procedures: Are New Age Modalities Set to Replace the Diagnostic Giant?

Abstract: ObjectiveThe goal of this study was to evaluate the diagnostic yield of B-mode ultrasound and ultrasound elastography used alone and in combination for differentiating breast lesions into benign and malignant. Materials and methodsEighty-five patients were investigated with B-mode ultrasonography and elastography and provided a Breast Imaging Reporting, and Data System (BI-RADS) score based on ultrasonography, strain ratio, and elastography score (ES) based on elastography. Each lesion was then evaluated by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Li et al [33] reported approximately 25% of phyllodes masses reporting an ES score more than 3. Similar false-positive results with phyllodes were reported by Khanduri et al [34] Li et al [33] has documented 5% of fibroadenoma to have an ES more than 3 as compared to 5.8% reported in our study.…”
Section: Gupta Et Alsupporting
confidence: 91%
“…Li et al [33] reported approximately 25% of phyllodes masses reporting an ES score more than 3. Similar false-positive results with phyllodes were reported by Khanduri et al [34] Li et al [33] has documented 5% of fibroadenoma to have an ES more than 3 as compared to 5.8% reported in our study.…”
Section: Gupta Et Alsupporting
confidence: 91%